Characterization and utilization of aqueous products from hydrothermal conversion of biomass for bio-oil and hydro-char production: a review - Usman, Muhammad; Chen, Huihui; Chen, Kaifei; Ren, Shuang; Clark, James H; Fan, Jiajun; Luo, Gang; Zhang, Shicheng (Green chemistry : an international journal and green chemistry resource : GC, 2019)
Hydrothermal conversion (HTC), including hydrothermal liquefaction and hydrothermal carbonization, is a cost-effective and environmentally friendly thermochemical technology for the utilization of biomass. Bio-oil and hydro-char have been the subjects of intense research over the past decade, during which considerable amounts of aqueous products with high concentrations of organics and nutrients have been produced, which have been largely overlooked. Compositions of hydrothermal conversion aqueous products (HTC-AP) strongly depend on the process conditions and biomass compositions, and also affect their further utilization. The present study systematically summarizes the main reactions occurring in HTC, characterization of HTC-AP, and factors affecting the compositions of HTC-AP. More importantly, recent advances of HTC-AP utilization techniques are summarized. Finally, the main challenges for future research on HTC-AP have been identified and possible solutions are given. Hydrothermal conversion (HTC), including hydrothermal liquefaction and hydrothermal carbonization, is a promising thermochemical technology for biomass utilization.